(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The researchers investigated the pair correlation function g(r) between sterically stabilized polystyrene particles in a binary mixture with poly (N isopropylacrylamide-co-acrylic acid) (pNipam-co-AAc) colloidal microgels as a function of temperature. The intensity peak of g(r) for polystyrene particles increases with increase in temperature indicating apparent attraction. The interaction potential ranges from repulsive at low temperature to attractive interaction as the temperature increases due to the collapse of the steric stabilizing surface layer, whose hydrogen bond is broken at low pH value. The experiment shows that tuning external factors in colloidal systems is possible to design complex materials that response to multicomponent